Association Between Proton Pump Inhibitors and Asthma: A Population-Based Cohort Study - Wang, Yao-Tung; Tsai, Ming-Chang; Wang, Yu-Hsun; Wei, James Cheng-Chung (Frontiers in Pharmacology, 2020)
ABSTRACT Objective: The relationship between proton pump inhibitors (PPIs) and asthma is controversial. The goal of this study was to determine the association between PPI use in non-asthma subjects and their subsequent asthma prevalence. Design: nationalwide, population-based cohort study Methods: We conducted a nationwide, population-based retrospective cohort study using data from the National Health Insurance Research Database (NHIRD) of Taiwan from 1999–2013. We identified 24077 adult patients with PPI use for more than 3 months and 24077 controls matched by propensity score on a one-to-one ratio for age, gender, comorbidities (hypertension, hyperlipidemia, gastroesophageal reflux disease, allergic rhinitis, atopic dermatitis, peptic ulcer disease, diabetes, and sleep apnea syndrome), and medications (histamine 2 receptor antagonists [H2RA], non-steroidal anti-inflammatory drugs [NSAIDs], and acetaminophen). The cumulative asthma incidence for the two cohorts in the follow-up period was estimated with the Kaplan-Meier method and the difference was examined using the log-rank test. Multivariate Cox regression models were used to calculate the adjusted hazard ratios (HR). Results: The overall incidence of asthma was 1.58-fold greater in the PPI cohort than in the non-PPI cohort (13.3 versus 8.4 per 1000 person-years), with an adjusted HR of 1.76 (95% confidence interval [CI], 1.64–1.88). In patients without previous peptic ulcer disease, the adjusted HR of asthma associated with PPIs was higher than in the non-PPI group (1.95; 95% CI, 1.80–2.11). The risk of asthma due to PPI use was also more significant in patients not receiving H2RA (1.81; 95% CI, 1.66–1.96), NSAIDs (1.93; 95% CI, 1.73–2.15), and acetaminophen (1.88; 95% CI, 1.70–2.08). Conclusions: This population base study demonstrated that patients with long-duration PPI use are at a higher risk of developing asthma, regardless of age, gender, comorbidities, and medications.